The Politics of Survival in Puerto Rico: The Balance of Forces in the Wake of Hurricane María (Alternautas, 2022)
Puerto Rico’s left-wing forces have long tried to unify, a goal that has proven difficult to reach and even harder to sustain. At its strongest, the Left has faced intense repression from both the United States and the island’s colonial government. Yet, activists and left-wing intellectuals agree that deeper differences account for the collective inability to build unity. Historically, left-wing forces in Puerto Rico have split over the national question. Pro-independence groups, arguably the largest sector, have prioritized decolonization while socialists, feminists, and environmentalists have proposed a broader anti-oppressive praxis centered on social and economic issues. Other groups, such as the Movimiento Socialista de Trabajadores, do not see these struggles as mutually exclusive, calling for the formation of a socialist republic in Puerto Rico. Today a new wave of Leftist organizing is emerging, one free from traditional Marxist or nationalist dogmas. This new Puerto Rican Left is organizing for economic justice and against colonialism while putting a greater emphasis on gender, sexuality, and race. It aims to foster young leadership, articulate new solidarities, and revive the practice of community organizing. It is learning from the errors of the past while picking up the sediments of previous struggles. Yet, if the Left wants to remain relevant, it must collaborate with the youth, student, community, feminist, farmer, and environmental justice groups that are bringing new energy to the island. This essay contextualizes the Puerto Rican Left in relation to the island’s political economy, identifies the forces in the Puerto Rican Left, reviews their differences and recent history, and presents a brief analysis of their political influence in Puerto Rican and US politics.